Estereótipos étnicos nas representações de crianças escolarizadas em São Luis do Maranhão - Sousa, Karla Cristina Silva (2009)
This dissertation discusses ethnic stereotypes. Stereotypes not related to ethnic narrative of adults, but the narrative of children.